Fungal Submerged Fermentation of Coffee Silverskin: A Sustainable Source of Natural Meat Additives - Stephany Carolina Terán-Rivera; Gastón Ramón Torrescano-Urrutia; Brisa del Mar Torres-Martínez; Martín Esqueda-Valle; Félix Joel Ibarra-Arias; Armida Sánchez-Escalante; Rey David Vargas-Sánchez (Resources)
The coffee industry, while processing coffee beans, generates residues like husk, pulp, and silverskin, which have been considered a promising source of bioactive metabolites. Recovering these metabolites offers a sustainable strategy to obtain natural food additives. Based on the above, this study aimed to determine the effect of the aqueous extract obtained from maceration and fungal fermented coffee silverskin (CSS) on ground pork meat’s oxidative and microbiological stability. Treatments used to recover bioactive compounds from CSS were the following: maceration extraction (ME) using 0, 1.5, and 3.0% of CSS (ME–0%, ME–1.5%, and ME–3%); fungal submerged fermentation extraction (FE) using 0, 1.5, and 3.0% of CSS (FE–0%, FE–1.5%, and FE–3%) and Pleurotus pulmonarius mycelium. Concerning metabolite content and bioactivity, results showed a decrease in the carbohydrate content of the ME and FE-obtained, as well as an increase in the phenol, flavonoid, and caffeoylquinic acid content. Also, an increase in radical cation scavenging activity, reducing power values and antibacterial activity of the extracts obtained with FE, was observed. Regarding pork meat homogenate treated with ME and FE extracts and subjected to oxidation with potassium ferrocyanide, results demonstrated that inclusion of FE-obtained extract led to decreased pH, lipid oxidation, metmyoglobin, and color changes (L*, a*, b*, C*, and h*), and microbial growth. These results demonstrate that CSS aqueous extract obtained with FE can be considered a potential additive for the meat industry with antioxidant and antibacterial activity. Nevertheless, further research is necessary to assess the sensory impact, biochemical mechanism, food safety, sustainability, and industrial feasibility of these extracts for broader applications.